Irrigation, settlement, and change on the Cache la Poudre River - Laflin, Rose, author; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 2005)
The Cache la Poudre River drains 1,890 square miles of land in the Mummy and Never Summer ranges in Colorado and Wyoming. It begins on the Continental Divide, flows through mountain canyons on the eastern side of the Rocky Mountains in Colorado and onto the plains, before joining the South Platte River. American settlers first diverted the Poudre’s water into ditches and canals to facilitate irrigation on the plains in the early 1860s. This examination of the water delivery system of the Cache la Poudre – which includes small ditches, large canals, and reservoirs – documents the use of the water for agriculture, municipal, industrial and recreational use. A synthesis of information from public sources such as university libraries, local history archives, the Colorado State Archives, the Colorado State University Water Resources Archive, and the Denver Public Library’s Western History Department, this “environmental history” addresses the development of the water delivery system; the impact of the delivery system on society, economy, laws, technology, hydrology, and the environment; and some attention to Colorado Water law.
June 2005.
Keywords: Irrigation canals and flumes -- Colorado; Cache la Poudre River (Colo.); Land settlement -- Colorado; Irrigation -- Research -- Colorado